PENERAPAN MODEL PEMBELAJARAN TAKE AND GIVE BERBANTUAN HANDOUT TERHADAP PENINGKATAN HASIL BELAJAR IPA PESERTA DIDIK KELAS IV SD NEGERI TIDUNG - Neneng Fitriani; Muh. Erwinto Imran; Ana Dhiqfaini Sultan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to determine the effect of implementing the Take and Give learning model assisted by handouts on the improvement of science learning outcomes of students. This research used an experimental method with a pre-experimental design in the form of a one-group pre-test–post-test design. The population of this study was 20 fourth-grade students of SD Negeri Tidung. The sampling technique used was convenience sampling, with the research subjects being fourth-grade students. The data collection technique employed was a pre-test and post-test. The data analysis used in this study was descriptive and inferential statistical analysis. The results showed that the application of the Take and Give learning model assisted by handouts had an effect on the science learning outcomes of fourth-grade students at SD Negeri Tidung. Based on the paired samples t-test, the significance value (2-tailed) was 0.000. This significance value is smaller than α (0.000 < 0.05). The average pre-test score was 45.50, while the post-test score was 87.00. Thus, it can be concluded that there was a significant difference in students’ average science learning outcomes between the pre-test and post-test using the Take and Give model assisted by handouts in the fourth grade of SD Negeri Tidung.